2017
DOI: 10.1088/2040-8986/aa9f50
|View full text |Cite
|
Sign up to set email alerts
|

Transverse linear and orbital angular momenta of beam waves and propagation in random media

Abstract: For paraxial propagation of scalar waves the classic electromagnetic theory definition of transverse linear (TLM) and orbital angular (OAM) momenta of the beam wave are represented in terms of the coherence function. We show in examples that neither the presence of optical vortices is necessary for the intrinsic OAM, nor does the presence of optical vortices warrant the non-zero intrinsic OAM. The OAM is analyzed for homogeneously coherent and twisted partially coherent beam waves. A twisted Gaussian beam has … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Equation ( 4 ) has the same basic form as a spatially twisted GSM beam 9 , 10 , 12 , 14 , 37 ; however, here, space and frequency are statistically twisted. It is well known that the spectral density of a spatially twisted stochastic source rotates as the beam propagates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation ( 4 ) has the same basic form as a spatially twisted GSM beam 9 , 10 , 12 , 14 , 37 ; however, here, space and frequency are statistically twisted. It is well known that the spectral density of a spatially twisted stochastic source rotates as the beam propagates.…”
Section: Methodsmentioning
confidence: 99%
“…Although evident from the numerous references describing rotating coherent beams 28 , 37 – 39 , it is important to point out that beam rotation does not imply partial coherence. Rotation, therefore, is a characteristic of partially coherent twisted beams, not a defining characteristic.…”
Section: Methodsmentioning
confidence: 99%
“…Scintillation index reduces with the increase of the topological charge it makes OAM beam, propagating longer distances [45], but mode scattering increases for higher order modes. Angular momenta is conserved for the free-space propagation [62] but not for an inhomogeneous medium. Scintillation severely impacts the operation of target designation [63] experiments done on the model simulations of discontinuity of statistical variations of atmospheric conditions.…”
Section: Effect Of Atmospheric Turbulence On Optical Signal Propagationmentioning
confidence: 99%
“…For quite a long time, it was believed that there exists a close interconnection between the spiral spectrum and phase vortex structures. However, Charnotskii's recent research showed that such a connection does not exist [5]. A tricky scenario is propagation in inhomogeneous media.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of turbulence can be described through the statistical moment of fluid parameters [10]. Consequently, by introducing statistical theory and assuming the media to be statistically homogeneous, it is deduced that the ensemble average of total OAM is conserved [5,9], while the spiral spectrum demonstrates a symmetric distribution with respect to the original [6][7][8]. Darryl J. Sanchez and Denis W. Oesch tentatively discussed the physical mechanism of the phenomenon: the kinetic energy of free turbulence dissipates as heat, which makes the spatial distribution of RI in turbulence inhomogeneous.…”
Section: Introductionmentioning
confidence: 99%